Comparative evaluation of lithium disilicate ceramic surface and bond strength to dentin surface after treatment with hydrofluoric acid and acidulated phosphate fluoride gel: An In Vitro study - D M Mallikarjuna; Surendra G B Kumar; Shilpa Shetty; Mallika Shetty; Bharath Raj (Wolters Kluwer Medknow Publications, 2018)
Context: Long-term retention of the restoration depends on strength and durability of the bond of the luting composite resin to the tooth and the porcelain substrates. Aims: This in vitro study was conducted to compare and evaluate the influence of hydrofluoric acid (HF) and acidulate phosphate fluoride (APF) gel-etched treatments on surface roughness and bond strength to dentin of a commercially available lithium disilicate ceramic (E-Max). Subjects and Methods: Sixty lithium disilicate ceramic disks measuring 5 mm in diameter and 2 mm thick were fabricated and divided into three groups: Group A (n = 24), Group B (n = 24), and Group C (n = 12) and were subdivided to Group A1, A2, and A3which were surface treated with 1.23% APF gel (pH = 3-4) at different time intervals 4, 7, and 10 min, respectively. Group B1, B2, and B3 were surface treated with 1% APF gel (pH = 1-2) at different time intervals 4, 7, and 10 min, respectively. Group C were surface treated with 9.6% HF (pH = 1-2) for 1 min. Morphological changes obtained with the surface treatments were analyzed using a surface profilometer. Statistical Analysis: All specimens were subjected to a tensile bond strength test using a tensometer, and the obtained data were statistically analyzed using Kruskal-Wallis test. Results: The surface roughness (μm) and bond strength (MPa) of lithium disilicate discs (samples) etched with 1.23% APF gel and 1% APF gel for 10 min and etched with 9.6% HF for 1 min showed no statistical significant difference among them. Conclusions: In this study, the lithium disilicate discs etched with 1.23% APF gel and 1% APF gel for 10 min showed similar surface roughness and bond strength to those etched with 9.6% HF for a minute.